Effects of Exogenous Surfactants on the Parameters of Blood Gas Composition in Neonatal Respiratory Distress Syndrome - S. A. Perepelitsa; A. M. Golubev; V. V. Moroz (Общая реаниматология)
Objective: to study the effects of the surfactants Surfactant-BL and Curosurf on pulmonary oxygenizing properties in preterm neonatal infants with respiratory distress syndrome (RDS). The studies were performed in 81 preterm neonates with severe RDS. For the therapy of RDS, the exogenous surfactants Surfactant-BL and Curosurf were used in 52 and 29 children with RDS, respectively. The similarity of infants from both groups was statistically confirmed. Blood gas composition and artificial ventilation parameters were examined. Results. The administration of the exogenous surfactants Surfactant-BL and Curosurf normalized blood gas composition, enhanced alveolar ventilation, and improved pulmonary ventilation-perfusion relationships. The exogenous surfactants permit the performance of artificial ventilation when the values are close to the physiological ones. There were no significant differences in the effects on the surfactants on gas exchange parameters. Key words: respiratory distress syndrome, surfactant, artificial ventilation, mean airway pressure, blood gas composition.